Hazards in Milling - Madlova, Danuse; Gebhart, Vlastislav (Manufacturing Technology Journal, 2017)
This paper is focused on hazards in milling processes. It continues in occupational health and safety in turning. Safety rules are based on general rules and specific ones which relate to milling. It is necessary to formulate hazard and safety rules more precisely for specific production processes and in some cases for different production machines. For satisfactory solution of this problem the rules are formulated on the base of laws, regulations and personal findings of the paper's authors in enterprises. In the paper occupational health and safety hazard rules in milling on these principles are formulated.
Keywords: Hazards; Occupational health and safety; Legislation; Milling